Technology supported rehabilitation for patients of critical illness caused by COVID-19: a protocol for a mixed-methods feasibility study. (2nd October 2020) - Gonçalves, Ana-Carolina; Leckie, Todd; Hunter, Alexander; Fitzpatrick, Daniel; Richardson, Alan; Hardy, Benjamin; Koulouglioti, Christina; Venn, Richard; Hodgson, Luke
Abstract : Background/Aims: The COVID-19 pandemic has created the need for research on how to effectively rehabilitate patients who have been discharged from an intensive care unit. This study is a protocol for a mixed methods feasibility study addressing the research questions: 1) what are the needs of patients who have survived COVID-19? 2) is the use of technology feasible to support their recovery? Methods: A multicentre, technology supported, rehabilitation intervention for survivors of critical illness caused by COVID-19 will be assessed. Survivors in the study population will be offered a smartwatch to monitor their activity levels and will have biopsychosocial outcome measures monitored at three time points: discharge from hospital, 2–3 months post discharge and 1 year post discharge. Semi-structured interviews will be conducted across eight hospital sites with survivors, their relatives and professionals to understand their recovery experiences. Conclusions: Designed by frontline clinicians, this protocol outlines a feasibility study that will provide new knowledge on the process of recovery of critical illness caused by COVID-19.